أثر التعزيز المستندي على اعداد تقارير مراجعي ديوان المحاسبة (Comprehensive Journal of Science, 2025)
This study aims to explore the impact of documentary support on the quality of audit reports issued by the Court of Accounts, focusing on the role of supporting documents in enhancing objectivity, accuracy, and strengthening financial oversight. The research adopts a descriptive-analytical approach, using a questionnaire as the primary tool for data collection from the auditors, and statistical analysis through distribution percentages, means, and standard deviations. The results indicate that the completeness and reliability of documents are key factors in enhancing the accuracy and objectivity of audit reports, while weak documentary support reduces the Court’s ability to detect financial irregularities and violations. The study also reveals that reliance on supporting documents increases stakeholders’ confidence in the reports and that there disparities in the level of attention to documentary support across different departments. Based on these findings, the study recommends establishing clear mechanisms to facilitate auditors’ access to supporting documents from the audited entities, thereby improving report quality and recommendation accuracy, and training auditors on the importance of precise documentation to ensure enhanced report quality and more effective financial oversight.
Keywords: Reports; Audit; Accounting; Documentation; Evidence; Quality; Oversight.